The robust peroxidase mimics within metal–organic frameworks for the sensitivity detection of H2O2 and glucose in serum. (8th October 2021) - Yang, Peipei; Ren, Qingfan; Chen, Yuying; Ouyang, Sixue; Huang, Zhipeng; Zhao, Peng; Tao, Jia
Abstract : Ultrafine and uniform CuPd alloy nanoparticles encapsuled in MOF to detect H2 O2 and glucose with a low detection limit. Abstract : Alloy nanoparticle-based nanozymes exhibit unique catalytic properties resulting from their tailored atomic coordination numbers and geometric parameters. The development of ultrafine alloy nanozymes is effective for improving their catalytic activities and promoting multifunction. However, it remains a challenge because of the aggregation of alloy nanoparticles resulting from the high surface free energy. This paper reports a strategy for stabilizing ultrafine and uniform CuPd alloy nanoparticles (2.18 ± 0.53 nm) in MIL-101 as a biosensor platform. The steady-state kinetic studies show that CuPd@MIL-101 can serve as a robust peroxidase-like nanozyme with a lower Michaelis constant ( K m ) than horseradish peroxidase (HRP). H2 O2 and glucose were chosen as model targets to develop a sensitive label-free colorimetric method using CuPd@MIL-101. The linear detection of H2 O2 in the range of 0.25–700 μM was achieved with a detection limit of 0.043 μM and that of glucose in the linear range of 0.5–400 μM with a detection limit of 0.16 μM. The catalytic activity of CuPd@MIL-101 can remain stable in the dulbecco's modified eagle's medium (DMEM) high-glucose medium and phosphate buffer solution (PBS) for at least five days. This study provides a meaningful reference for developing ultrafine nanozymes without affecting their stability.